2015
DOI: 10.1080/15592294.2015.1029700
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian randomization supports causality between maternal hyperglycemia and epigenetic regulation of leptin gene in newborns

Abstract: Leptin is an adipokine that acts in the central nervous system and regulates energy balance. Animal models and human observational studies have suggested that leptin surge in the perinatal period has a critical role in programming long-term risk of obesity. In utero exposure to maternal hyperglycemia has been associated with increased risk of obesity later in life. Epigenetic mechanisms are suspected to be involved in fetal programming of long term metabolic diseases. We investigated whether DNA methylation le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 53 publications
1
72
2
1
Order By: Relevance
“…Our results did not demonstrate a direct association between decreased LEP methylation and increased neonatal cord blood leptin levels or adiposity measures, as reported by Allard and colleagues . Allard's cohort included women with gestational diabetes, and analyses demonstrated that a higher maternal glycaemia risk score was associated with decreased LEP methylation and higher cord blood leptin levels.…”
Section: Discussioncontrasting
confidence: 59%
“…Our results did not demonstrate a direct association between decreased LEP methylation and increased neonatal cord blood leptin levels or adiposity measures, as reported by Allard and colleagues . Allard's cohort included women with gestational diabetes, and analyses demonstrated that a higher maternal glycaemia risk score was associated with decreased LEP methylation and higher cord blood leptin levels.…”
Section: Discussioncontrasting
confidence: 59%
“…It is believed that epigenetic mechanisms involving leptin surge during the perinatal period in response to maternal hyperglycemia plays a pivotal role for fetal programming of adult onset metabolic disorders including obesity. DNA methylation near the leptin gene locus seems to control the correlation between maternal glycemic levels and neonatal leptin with high cord blood levels of leptin associated with lower DNA methylation at cg12083122 (Allard et al, 2015).…”
Section: Genome-wide Analysis and Obesitymentioning
confidence: 97%
“…Maternal glycaemia is part of causal pathways influencing offspring leptin epigenetic regulation [80]. Moreover, it was demonstrated that LEP promoter DNA methylation is influenced by perinatal factors including: maternal obesity, infant growth, genotype and gender in a tissuespecific manner [81].…”
Section: Epigenetic Regulation Of Leptin-related Signalling Pathways:mentioning
confidence: 99%